UNGKAPAN LARANGAN BAGI SUAMI KETIKA ISTRINYASEDANG HAMIL DI KENAGARIAN ALAHAN PANJANG KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Rahmawita Rahmawita; Nurizzati Nurizzati; Muhammad Ismail Nasution (Faculty of Languages and Arts, Universitas Negeri Padang, 2013)
This research aims to describe the structure, categories and social functions contained in the expression for the ban on husband while his wife was pregnant at Alahan Subdistrick Panjang Lembah Gumanti Regency Solok . This research descriptive qualitative research method.The background of this study was , while the entry of this study is the expression in Kenagarian Alahan Panjang Subdistrick Lembah Gumanti Regency Solok ban on the husband in terms of structure, categories and social functions. To collect the data acquisition from Kenagarian Alahan Panjang Subdistrick Lembah Gumanti Regency Solok the informants using recording techniques. The technique used to analyze the data as follows. (1), transcribes the data from spoken language into written language, (2), translates the data into Indonesian. (3), analyzing the structure of the expression for the ban on husband while his wife was pregnant. (4), analyzed the expression category prohibition for a husband when his wife was pregnant. (5), to analyze the social function expressions prohibition for a husband when his wife was pregnant. (6), formulating research results in the form of reports.